Differential Neuropsychological Profile of Patients With Amyotrophic Lateral Sclerosis With and Without C9orf72 Mutation. (5th January 2021) - Iazzolino, Barbara; Peotta, Laura; Zucchetti, Jean Pierre; Canosa, Antonio; Manera, Umberto; Vasta, Rosario; Grassano, Maurizio; Palumbo, Francesca; Brunetti, Maura; Barberis, Marco; Sbaiz, Luca; Moglia, Cristina; et al.
Abstract : Objective: To determine whether the neuropsychological profiles of patients with amyotrophic lateral sclerosis (ALS) with (ALSC9+) and without (ALSC9−) C9orf72 expansion are different, we administered a battery of neuropsychological tests to 741 patients with ALS (68 ALSC9+ and 673 ALSC9−) and 129 controls. Methods: The study population includes 741 patients with ALS who were consecutively diagnosed at the Turin ALS expert center in the 2010–2018 period and who underwent both cognitive/behavioral and genetic testing. Patients' neuropsychological patterns were compared (1) at the same degree of cognitive and behavioral deficit according to the revised ALS–Frontotemporal Dementia Consensus Criteria and (2) at the same level of motor impairment according to the King staging system. Results: Despite being about 7 years younger, ALSC9+ patients had significantly lower scores in tests exploring executive function and verbal memory both when classified as cognitively normal and when diagnosed in the intermediate cognitive categories. Considering the clinical perspective, ALSC9+ patients showed significantly lower scores compared to ALSC9− patients at King stage 1 and 3 in almost all the examined neuropsychological domains; at King stage 2, ALSC9+ patients were more severely affected only in the verbal memory domain. Behavioral function was comparably impaired in the 2 cohorts. Conclusions: ALSC9+ patients show a different neuropsychological profile compared to ALSC9− patients, being more impaired in executive functions and verbal memory domains at all King stages. Verbal memory emerged as a particularly vulnerable function in ALSC9+, with worse performances even when patients were still classified as cognitively normal.